AN ANALYSIS SEMANTIC OF LEXICAL AND CONTEXTUAL MEANING OF MAHER ZAIN’S SONG - yuliana, Eva (Universitas Madura, 2024)
Semantics is a sub discipline of linguistics which focuses on the study of meaning. The present study analyzes about semantics analysis especially on the lexical meaning and contextual meaning. The lexical meaning is to be interpreted as the meaning of lexemes depending on the meaning of sentences which they occur.lexical meaning is the meaning of the word when the word is seen separately, either in form or form a lexeme affix whose meaning is more or less fixed, as can be read in a certain passage dictionary. Contextual meaning could be regarded as a situational meaning. It arised as a result of the relationship between speech and context. It took the form of a lot of things. This study aim to describe lexical and contextual meaning. This study is uses descriptive qualitative method. The informants used data source, data collection, and data analysis.get a short strory about this song and they are known about the theme of this song.